Diversification of Gorontalo Cake Products (Belekoa) In Order to Increase Income for The Group of Businesses Together in Gandaria Village, Tolangohula District, Gorontalo District - Dungga, Meriyana Fransisca; Bokingo, Agus Hakri (AIBPM Publisher, 2019)
Today's society is undergoing a very rapid and complex change, due to advances in science and technology. Overall change occurs in almost all aspects of life. The job market has changed dramatically, both due to the influence of information and global technology. Changes that are so fast have an impact on the demands of society. The impact of these changes requires changes in patterns and institutional management strategies that are more appropriate, so that they can provide an appropriate response to the challenges that exist. Likewise, what happens in the management of the Production Unit requires effort in order to develop it. Guidance on product development and its quality is needed. Product development (produck development), basically is an effort to always create new products, improve old products in order to meet market demands and customer tastes. The demands and desires of customers always develop in line with the development of science, technology and information, therefore developing products, including product diversification is a challenge that must be sought. Customers need products that are always new and specific. To realize this, continuous innovation is needed so that the production unit as a business will continue to live and develop.